Kemampuan Literasi Muzakki Dan Penerapan Psak 109 Dalam Kepercayaan Untuk Berzakat Pada Organisasi Pengelola Zakat (OPZ) - Hastuti Olivia; Annisa Namira; Dominggus Sijauta; Nadratul Hasanah Lubis; Syahrijal Hidayat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Public literacy about zakat institutions is very important to increase knowledge and management of zakat institutions. The purpose of this study was to determine literacy, the application of PSAK 109 and the trust of muzzaki in giving zakat at OPZ. This study used a quantitative method with a population of 48 respondents and data processing using SPSS 22. The results in this study the literacy variable has an effect on trust, the application of PSAK 109 has an effect on trust as well as the literacy variable, the application of PSAK 109 has a simultaneous effect on trust. Muzzaki's trust is needed to increase OPZ's income to alleviate poverty in Indonesia.